A shock to the system - Hayes, J (Reuters Institute for the Study of Journalism, Department of Politics and International Relations, University of Oxford, 2009)
The Freedom of Information Act 2000 has changed journalism in Britain; for a number of journalists it has altered the way they work and their expectation about the information they can gather through it. Four years after the Act was introduced, the flow of news stories relying in whole or in part on information gained through a request has become continual. The purpose of this research is to evaluate the way in which the Act is being applied by officials and the uses to which it is being put by journalists.